Crowd Logistics - A Literature Review and Maturity Model - Jens Mehmann; Volker Frehe; Frank Teuteberg (Innovations and Strategies for Logistics and Supply Chains: Technologies, Business Models and Risk Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 20, 2015)
Crowd Logistics (CL) is identified as a topic of high importance in the area of logistics. From the practical point of view, initial experiences and realizations have already been gained, however, scientific research regarding Crowd Logistics is still in its infancy and multiple research questions are still unexplored. By means of a systematic literature review (LR) as well as a quantitative data analysis (QDA) of existing business models, we obtained a scientific definition of the term Crowd Logistics. Furthermore, we set up a research agenda to counter the open research questions. Additionally, based on the results of the LR and the QDA as well as the knowledge gained in field studies, we developed a Crowd Logistics Maturity Model (CLMM). We evaluated the CLMM by the use of an existing company.
10419/209189; https://econpapers.repec.org/RePEc:zbw:hiclpr:20
Keywords: 650; Crowd Logistics; Maturity Model; Literature Review; Qualitative Data Analysis